THE EFFECT OF JACK FRUIT(Artocarpusheterophyllus) ADDEDTOCATFISHNUGGET (Clariasgariepinus) ON THE CONSUMER ACCEPTANCE. - Sarli Marselina; Desmelati Desmelati; N Ira Sari N Ira Sari (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACTThis study aimed to determine the effect of addition of jackfruit to the catfish nugget on the consumer acceptance. The research was conducted by using experimentally method by processing nugget of the catfish with the addition of jackfruit in different amount, those were 50, 75 and 100 gram. The result showed that the addition of 50 gram jackfruit to the catfish nugget was indicating the highest consumer acceptance. The appearance was accepted by 92,49% (74 panelist), with the criteriawas bright yellow and attractive. The aroma was accepted by  76.25% (61 panelist) with the criteria was not too strong according to the aroma of the fish. The taste was accepted by93.75% (75 panelist) with the criteria of taste was delicious, tasty, and still feel the fish tasted. The texture was accepted by87.5% (70 panelist) characterized by the solid very compact, and chewy. The content of protein was 16,80%, fat 7,94%, water 42,51%, ash 2.09%,  and coarse fiber content 2.00%.Keywords:  Consumer acceptance, dumbo catfish, fish nugget, jackfruit